Osteocyte size, shape, orientation, and population density - Skedros, J. G.; Weaver, D. J.; Doutré, M. S. (Osteologie, 2016)
Despite being encased in lacunae, osteocytes are extensively interconnected and have several mechanisms that enable them to physically and chemically appraise their environment and adjust to it. In the perspective that cell-cell and cell-matrix interactions mediate these functions and are critically important during the formation of a mechanically competent bone organ, we focus on several considerations: (1) osteocyte lacunae are not always occupied by living cells and the percent lacuna vacancy can increase with aging, some diseases, and experimental perturbations, (2) the potential for the population density and/or sizes and shapes of osteocytes (or of their lacunae) and of their cell processes (typically seen as the canaliculi in which they reside) in helping investigators interpret the load history of a bone or bone region, and (3) scaling relationships between osteocyte density and various parameters, including animal mass and metabolism. We also point out that all of these considerations are being impacted by high-resolution three-dimensional imaging technologies that allow increased accuracy when quantifying details of lacunar-canalicular geometries.
Keywords: Osteocyte; osteocyte lacuna; canaliculi; osteons; osteon morphotypes; bone